Development of unilateral obstacle-avoiding mower for Y-trellis pear orchard - Lei, Xiaohui; Qi, Yannan; Zeng, Jin; Yuan, Quanchun; Chang, Youhong; Lyu, Xiaolan (International Journal of Agricultural and Biological Engineering, 2022)
To solve the problem of weeding under Y-trellis pear orchards, a unilateral obstacle-avoiding mower (UOAM) was developed in this study. The mower is composed of an obstacle-avoiding disc mechanism, a hydraulic profiling mechanism, and a cutting disc mechanism. The diameter of the obstacle-avoiding disc was 0.7 m, which could swing around the trunk or ground pile actuated by the spring mechanism. The piston movement of the hydraulic cylinder controls the working position of the obstacle-avoiding disc. The maximum extension distance of the hydraulic profiling arm was 1 m. Based on the national standards and actual situation of orchards, the optimum parameters were determined with a combination of advancing speed of 0.44 m/s, rotation speed of the cutting disc at 2000 r/min, blade number of 2, and cutting edge length of 0.2 m. Finally, the design parameters were verified by the mathematical model of the blade cutting edge trajectory and multi-body dynamics simulation. Taking stubble cutting stability, leakage rate, working efficiency and costs as the test indexes, field performance comparison tests were carried out on the three operation modes of UOAM mowing, shoulder carrying mower (SCM) mowing and manual weeding. Test results showed that the coefficient variation of stubble cutting height of UOAM was the smallest, showing that the working stability of UOAM was better than the other two treatments. The leakage rate of UOAM was 2.42%, and its coefficient variation was lower than that of SCM. The working efficiency of UOAM was much higher than that of SCM and manual weeding, which was 4.44 times of SCM and 20 times of manual weeding. The profitable area of UOAM was 7.02 hm2, showing that it was suitable for large-scale mechanized Y-trellis pear orchards. Keywords: unilateral obstacle-avoiding mower, Y-trellis pear orchard, movement trajectory, working performance DOI: 10.25165/j.ijabe.20221501.7013 Citation: Lei X H, Qi Y N, Zeng J, Yuan Q C, Chang Y H, Lyu X L. Development of unilateral obstacle-avoiding mower for Y-trellis pear orchard. Int J Agric & Biol Eng, 2022; 15(1): 71–78.